2016
DOI: 10.4149/neo_2016_009
|View full text |Cite
|
Sign up to set email alerts
|

10-Hydroxycamptothecin induces apoptosis in human neuroblastoma SMS-KCNR cells through p53, cytochrome c and caspase 3 pathways

et al.

Abstract: Neuroblastoma (NB), the most common extracranial solid tumor in childhood, remains one of the most challenging types of cancer to treat. Therefore, the search for novel effective drugs for its treatment is essential. The present study used 10-hydroxycamptothecin (HCPT), which is a naturally occurring alkaloid anticancer agent extracted from the Chinese tree, Camptotheca acuminata, and has a strong anticancer activity in vitro and in vivo. HCPT is able to induce apoptosis in cells of various tumor types. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Our study also displayed CytC overexpression after Eca cells were treated with Tan IIA (20, 40, 60 μg/mL) for 72 hours (Figs ). These results are consistent with findings by other researchers, implying that CytC overexpression most probably participates in Tan IIA‐induced Eca‐109 cell apoptosis . It is well known that caspase activation is generally considered a key characteristic of apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also displayed CytC overexpression after Eca cells were treated with Tan IIA (20, 40, 60 μg/mL) for 72 hours (Figs ). These results are consistent with findings by other researchers, implying that CytC overexpression most probably participates in Tan IIA‐induced Eca‐109 cell apoptosis . It is well known that caspase activation is generally considered a key characteristic of apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…PARP can also induce programmed cell death by producing poly-ADP-ribose [PAR] through stimulating mitochondria to release apoptosis-inducing factor (AIF) [31]. Herein, PARP promoted the inhibition of Bcl-2 and triggered the release of Bax and cytochrome C (Cyt-C), promoting apoptosis [32,33]. In this study, cytotoxic activity of escitalopram oxalate was initiated by activating caspase-8 and cleaving caspase-3, resulting in the proteolytic cleavage of PARP in U-87MG cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was revealed that HCPT effectively promoted caspase-3/9 activities and inhibited the protein expression of Bcl-2 in human osteosarcoma MG-63 cells. Yuan et al (12) had previously indicated that HCPT induces apoptosis through the p53, cytochrome c and caspase-3 pathways of human neuroblastoma SMS-KCNR cells.…”
Section: Discussionmentioning
confidence: 99%
“…The primary negative effects include myelosuppression and a gastrointestinal reaction. These effects are due to dose-limiting toxicity (12). Currently, HCPT is primarily used in the form of a sodium salt injection.…”
Section: Introductionmentioning
confidence: 99%